Grand challenges at the frontiers of fish science - McKenzie, David J.; Aarestrup, Kim; Domenici, Paolo; Fanelli, Emanuela; Mourier, Johann; Tsigenopoulos, Costas S. (Frontiers in Fish Science, 2024)
We provide a review of what we consider to be grand research challenges for fish science in an era of human-induced rapid environmental change.